Idiosyncratic risk, aggregate risk, and the welfare effects of social security - Daniel Harenberg; Alexander Ludwig (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
We ask whether a pay-as-you-go financed social security system is welfare improving in an economy with idiosyncratic productivity and aggregate business cycle risk. We show analytically that the whole welfare benefit from joint insurance against both risks is greater than the sum of benefits from insurance against the isolated risk components. One reason is the convexity of the welfare gain in total risk. The other reason is a direct risk interaction which amplifies the utility losses from consumption risk. We proceed with a quantitative evaluation of social security's welfare effects. We find that introducing an unconditional minimum pension leads to substantial welfare gains in expectation, even net of the welfare losses from crowding out. About 60% of the welfare gains would be missing when simply summing up the isolated benefits.
urn:nbn:de:bsz:180-madoc-456523
Keywords: C68; E27; E62; G12; H55; 330; social security; idiosyncratic risk; aggregate risk; welfare